Perbandingan harga saham, volume transaksi dan return saham sebelum dan sesudah terjadi pandemi covid-19 pada PT Agung Podomoro Land, Tbk - Anggun Putri Romadhina; Eka Kusuma Dewi (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2021)
The first Covid-19 case in Indonesia was announced on March 2, 2020. This study aims to determine whether there is a significant difference in stock prices, stock transaction volume and stock returns due to the COVID-19 pandemic (case study at PT. Agung Podomoro Land, Tbk). This research data was taken 90 days before and 90 days after the announcement of the first case of COVID-19 in Indonesia. The data was processed by paired sample t-test, using SPSS version 20. From the results of data processing, it was shown that there was a significant difference in stock prices before and after the announcement of the first case of covid-19 in Indonesia. This is indicated by a significance value of 0.000 < 0.05 where the stock price has decreased compared to before the Covid-19 case. Meanwhile, the volume of stock transactions also showed a significant difference with a significance value of 0.007 <0.05, where the volume of stock transactions after the announcement showed a decrease. Likewise, stock returns show a significant difference with a significance value of 0.025 < 0.05 where stock returns have decreased after the announcement of the first case of covid-10 in Indonesia.